Serum levels of soluble CD163 and soluble CD14 following antibiotic therapy of patients with acute brucellosis - Huali Sun; Rongmeng Jiang; Bing Han; Xiufang Du; Chengjie Ma; Yanli Xu; Zhihai Chen; Linghang Wang; Siyuan Yang; Xiao Lv; Hong Zhao; Xingwang Li (Journal of Infection in Developing Countries)
Introduction: Soluble CD163 (sCD163) and soluble CD14 (sCD14) levels, monocyte/macrophage activation markers, are elevated in patient serum during Brucella infection. The aim of this study was to measure serum sCD163 and sCD14 levels during treatment for acute brucellosis to determine whether they can be used to monitor treatment efficacy.